The Base in the Computation of DFL - Berent, Tomasz (Baza w obliczaniu DFL, 2011)
The degree of financial leverage DFL is one of the most popular leverage ratios used in literature. As an elasticity ratio, DFL informs about the scale of net profit relative (percentage) reaction to a 1% change in operating income. This paper focuses on the base value of profit necessary for the computation of DFL. The issue is important as the choice of the base numbers determines the value of DFL. It is argued in the paper that DFL should be regarded merely as a language convention, which communicates the changes in profitability. As such DFL can be sometimes useful as a tool in financial analysis. It is the discretionary nature of the base selection which subsequently determines the value of DFL, which, among other arguments, suggests that DFL should not be regarded as a risk measure in the sense used by the modern finance theory.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 904-919
Keywords: financial leverage; degree of financial leverage; financial risk